THE NETWORK EMBEDDEDNESS OF A FOREIGN SALES SUBSIDIARY The subsidiary personnel perspective - Aho, Laura (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
This study focuses on the network embeddedness of a subsidiary of a multinational company. Academic research has identified the rising role of geographically dispersed subsidiaries as valuable sources of strategic knowledge and value to the whole multinational company. Moreover, previous research suggests that in order to gather this knowledge and transfer it across the multinational company, a subsidiary needs to be insider, i.e. embedded, in both its local external network as well as in its internal corporate network. The purpose of this study is to describe the network embeddedness of a foreign sales subsidiary from the subsidiary personnel perspective and hence increase understanding on the phenomenon and provide suggestions to enhance overall subsidiary embeddedness. The empirical study was based on a theoretical framework on subsidiary network embeddedness and comprised a qualitative single-case study in a French sales subsidiary of a Nordic multinational company. Data collection included nine semi-structured interviews and six Network Pictures drawing tasks. Altogether eight people out of subsidiary staff of eleven participated in the study providing relatively exhaustive overview of the subsidiary personnel perspective. Based on the collected data, the relationships toward the most relevant network actors, both internal and external were identified and their impact on the subsidiary embeddedness were analyzed separately. Moreover, the subsidiary’s simultaneous embeddedness in both internal and external network, that is, the subsidiary dual embeddedness, was discussed to increase understanding how subsidiary personnel perceive their role between the two networks and its impact on the subsidiary activities. The findings of the study suggest that the subsidiary personnel perceives strong external embeddedness increasing internal and dual-embeddedness since intensive external collaboration requires including and activating other corporate units as well. The role of the local sales subsidiary is to act as the interpreter and connector between the internal and external network actors. Hence, by actively promoting relationship linkages between internal and external actors, the subsidiary may adopt an active role beyond its original corporate mandate. In order to achieve this, both managers on the subsidiary and corporate level need to promote open communication and increase cultural understanding between different corporate units.